Morpho-taxonomy, behaviour and ecology of the Rajah Brooke’s birdwing (Trogonoptera brookiana) in Peninsular Malaysia / Phon Chooi Khim - Phon , Chooi Khim (2018)
The Rajah Brooke’s Birdwing, Trogonoptera brookiana is a well-known ecotourism icon. However, habitat degradation and over collecting have threatened the existence of this birdwing, necessitating an in-depth study of the species. This research investigated the taxonomy, behaviour and ecology of the subspecies albescens and mollumar in Peninsular Malaysia, with the intention of enhancing conservation efforts. The status of the eastern peninsular population of Trogonoptera brookiana, described as a new subspecies mollumar D’Abrera has in the past been debated, resulting in it being synonymised with the Sumatran subspecies, trogon Vollenhoven. The findings from this work elucidate without doubt distinguishable taxonomic characters that support the re-instatement of its subspecific status. The distribution of subspecies albescens and mollumar was assessed and seen to be shrinking, reflecting a population decline, when contrasting the recent (year 2000 onwards) and earlier (before year 2000) extent of its distribution. To assist in understanding this insect and in its conservation, behavioural studies were conducted. The subspecies albescens was studied in two selected sites, that is Ulu Geroh village and Kenaboi Forest Reserve. Detailed information on daily activity rhythms, such as flight and puddling behaviour in relation to environmental variables was revealed by the study. The interactions between males and females were studied ad libitum during all the field works. The birdwings preferred Bauhinia flowers over hibiscus, but more interestingly, there were differences between sexes in their nectaring rhythm in relation to feeding bouts and social feeding behaviour. All the interactions between males and females were initiated by males, and competition for mates was a common phenomenon. Different mate locating strategies were applied by the males in different localities. Some acceptance and rejection behaviours by females were documented. A novel monitoring method using digital photography, was developed for the puddling males of subspecies albescens in Ulu Geroh, and tested for 24 months. It showed for the first time that puddling activity can be used as a population index. The birdwing population fluctuated greatly during monitoring, with peaks in May for both years and an additional peak in the month of August in the second year. The population counts were significantly associated with monthly mean temperature. Additionally, transect walk and single-point observation methods were utilised to monitor birdwings in flight in Kenaboi Forest Reserve, generating 29-months of monitoring data at this site. The results reported here will aid in the formulation of conservation measures for this charismatic birdwing species that has great potential as an ecotourism icon in this region.